Pengembangan Keterampilan Berpikir Kritis Dan Pemecahan Masalah: Mengapa Hal Ini Penting Dan Bagaimana Cara Melakukannya - Hafriani; Rawi Juanda; Cut Ratna Dewi; Munirul Hady (JKA, 2024)
This study aims to assess the effectiveness of the application of problem-based learning model or Problem Based Learning in improving the ability to think critically and problem solving in students. The method used in this study is the study of literature by reviewing several relevant sources. The results showed that the problem-based learning model proved effective for improving critical thinking and problem solving skills in students. Through the stages of learning that exist in Problem Based Learning, students will be accustomed to observe, ask questions, analyze, collect information, process information,and communicate the results of their thinking so that the ability to think critically and problem solving students will grow. Therefore, teachers are expected to apply problem-based learning models to develop students ' critical thinking and problem-solving skills.